The impact of diabetes on the association between alcohol intake and the risk of end‐stage kidney disease in the Singapore Chinese Health Study. Issue 8 (25th March 2020) - Geng, Ting‐Ting; Jafar, Tazeen Hasan; Yuan, Jian‐Min; Koh, Woon‐Puay
Abstract: Background: The relationship between alcohol intake and end‐stage kidney disease (ESKD) risk is controversial. Moreover, while evidence has shown that the relationship between alcohol and atherosclerosis may be modified by diabetes, whether this applies to ESKD is unknown. Methods: We examined these associations in the Singapore Chinese Health Study, a prospective cohort of 63 257 adults aged 45 to 74 years. Information on alcohol intake, diet, lifestyle factors, and medical history was collected at recruitment. We identified 1217 ESKD cases via linkage with the Singapore Renal Registry after a mean follow‐up of 17.5 years. Cox regression models were used to estimate hazard ratios (HRs) and 95% CI of ESKD. Results: Among the participants without diabetes at baseline, monthly to weekly drinking was associated with a decreased risk of ESKD (HR 0.69; 95% CI, 0.54‐0.87) compared to nondrinkers. In contrast, this association was attenuated and not significant among those with diabetes (HR 0.82; 95% CI, 0.58‐1.16; P interaction = .19). Comparatively, alcohol intake of ≥2 drinks per day was significantly associated with an increased risk of ESKD compared to nondrinkers among those with diabetes (HR 2.00; 95% CI, 1.14‐3.53) but not among those without diabetes (HR 0.91; 95% CI, 0.53‐1.56; P interaction = .01). The risk of ESKD among those with diabetes and who also consumed ≥2 drinks per day was increased by nearly 12‐fold compared to nondrinkers without diabetes (HR 11.6; 95% CI, 6.73‐19.9). Conclusion: Low‐dose drinking is associated with a reduced risk of ESKD among individuals without diabetes. However, joint exposure to heavy drinking and diabetes is associated with a substantially higher risk of ESKD. Abstract : Highlights Low‐dose intake of alcohol is associated with a lower risk of end‐stage kidney disease (ESKD) in nondiabetic participants. Joint exposure to heavy drinking and diabetes is associated with a substantially higher risk of ESKD. Recommendations on alcohol intake among patients at risk of ESKD should consider the presence of diabetes as a comorbidity. 摘要: 背景: 酒精的摄入与终末期肾病(ESKD)风险之间的关系仍存在着争议。此外, 有证据表明糖尿病可能会影响酒精与动脉粥样硬化之间的关联, 但这是否适用于ESKD尚不清楚。 方法: 利用前瞻性队列"新加坡华人健康研究"探讨酒精的摄入与ESKD风险的关联, 该研究由63257名45‐74岁的成年人组成。基线收集了关于酒精摄入量、饮食习惯、生活方式及疾病史的资料。经过平均17.5年的随访, 通过新加坡肾脏病登记处的链接, 确定了1, 217例ESKD病例。使用比例风险(Cox)回归模型估算ESKD的风险比(HRs)和95%置信区间(CI)。 结果: 在无基线糖尿病的参与者中, 与非饮酒者相比, 每月至每周饮酒与ESKD风险降低相关(HR 0.69, 95%置信区间0.54‐0.87)。相反, 该关联在基线糖尿病患者中减弱并且不再显著(HR 0.82, 95%置信区间0.58‐1.16; P交互作用= 0.19)。相比之下, 在基线糖尿病患者中, 与非饮酒者相比, 每天摄入≥2个标准饮酒单位与ESKD风险增加显著相关(HR 2.00, 95%置信区间1.14‐3.53), 而在无基线糖尿病参与者中无统计学意义(HR 0.91, 95%置信区间0.53‐1.56; P相互作用= 0.01)。与无基线糖尿病的非饮酒者相比, 患有糖尿病且每天饮酒≥2个标准饮酒单位的人患ESKD的风险增加了近12倍(HR 11.6, 95%置信区间6.73‐19.9)。 结论: 在非糖尿病患者中, 低剂量饮酒与ESKD风险降低显著相关。然而, 大量饮酒和糖尿病的联合效应与ESKD的风险大幅增高显著相关。